Oil Revenue, Institutional Quality and Economic Growth in Nigeria - Balogun, Afolabi Q.; Obele, Tolulope E.; Adeniyi, Toibu M. (ABUAD Journal of Social and Management Sciences, 2024)
This study examined the interaction of oil revenue and institutional quality on economic growth in Nigeria over the period of 1993 - 2022. The World Development Indicator (WDI) and the Central Bank of Nigeria (CBN) statistical bulletin were the sources of the annual time series data used in this study. Employing the Autoregressive Distributed Lag (ARDL) estimation technique, findings reveal that oil revenue impacts economic growth positively in the short-run but negatively in the long run, while institutional quality exhibits positive impact in both the short-run and long-run period. It was also discovered that the interaction of oil revenue and economic growth could enhance economic growth in Nigerian both in the short-run and long-run period. Access to clean fuels and technologies contributes positively to economic growth in both short-run and long-run period, while fiscal policy rating only has statistically significant positive association with economic growth in Nigeria over the observed period. This study therefore recommends the need to strengthen political institutions for effective utilization of oil revenue, and implementation of strategic diversification policies for the development of other sectors in the economy for economic prosperity in Nigeria.